New Record of the Species Synthesiomyia Nudiseta (van der Wulp, 1883) (Diptera, Muscidae) with Forensic Study from Kerbala City, Iraq - Naeem Al-Ashbal1 , Rafid Abbas Al-Essa1 , Hanaa H. Al-Saffar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study aimed to investigate Synthesiomyia nudiseta (van der Wulp, 1883) in the carcasses of dogsand rats in four different localities of Kerbala governorate. during four seasons. The results indicated theappearance of S. nudiseta only in the spring and autumn seasons within the urban and agricultural areas, aswell as the appearance of this species on the bodies of dogs only without rats. Taxonomy and morphologicalfutures were described. S. nudiseta is belonging to the family Muscidae (Order: Diptera) is described as afirst time recorded in Iraqi entomofuna. The specimens wear collected from carcasses of dogs and rats atagriculture and urban regions of Kerbala city. The diagnostic characters and mean morphological featureswere photoed.